International maritime transport : perspectives - McConville, J.; Morvillo, Alfonso; Leggate, Heather (Routledge advances in maritime studies, 2005)
"The importance of the international maritime transport industry is difficult to overstate. This new book presents an interdisciplinary approach from a wide range of internationally based experts. International Maritime Transport includes chapters on topics across the spectrum of integrated subjects (non-sector specific subjects) supplemented with contemporary articles and papers." "The book is sure to be of great interest to students and academics working on maritime studies, as well as being extremely useful to professionals and policymakers in the maritime industry."--Jacket